O
olahauan
![](https://blog.hocmai.vn/wp-content/uploads/2017/07/hot.gif)
![](https://blog.hocmai.vn/wp-content/uploads/2017/07/hot.gif)
bài 1 :cho $\dfrac{a}{b} = \dfrac{ c }{ d }$
Cm:
a) $\dfrac{a+2006b}{a-2006b} = \dfrac{c+2006d}{c-2006d}$
b) $\dfrac{2006(a+c)}{2006a} = \dfrac{b+d}{b}$
bài 2 : Cm : nếu $\dfrac{a+2006}{a-2006} = \dfrac{b+2005}{b-2005}$ thì $\dfrac{a}{b} = \dfrac{2006}{2005}$
Chú ý : Gõ Latex
P.s : Đã sửa
Cm:
a) $\dfrac{a+2006b}{a-2006b} = \dfrac{c+2006d}{c-2006d}$
b) $\dfrac{2006(a+c)}{2006a} = \dfrac{b+d}{b}$
bài 2 : Cm : nếu $\dfrac{a+2006}{a-2006} = \dfrac{b+2005}{b-2005}$ thì $\dfrac{a}{b} = \dfrac{2006}{2005}$
Chú ý : Gõ Latex
P.s : Đã sửa
Last edited by a moderator: